This article explains the process of managing Covid-19 funds in several regions in Indonesia. Using the grand theory of open government and qualitative approaches to the type of literature study research, researchers conducted data collection to be able to explain the importance of using Open Government through open data initiatives in order to manage the Covid-19 budget and avoid potential corruption. The Covid-19 pandemic that has hit Indonesia since the beginning of March 2020, has directly e - Rizki Zakariya (Journal of Governance Innovation, 2021)
The disruption of the economic life of rural communities is the impact of the current Covid-19 Pandemic. So that it is detrimental to the economic gains of the village community. Therefore, to alleviate this impact, the Government has launched a program to utilize village funds for direct cash assistance for village communities. However, the implementation of the program has a gap in corruption. So it is necessary to make efforts to prevent this corruption, in order to streamline the provision of direct cash assistance to the public. The method used in this research is descriptive qualitative with a case approach and a statute approach. Furthermore, the legal materials used are primary and secondary legal materials. Then a qualitative analysis was carried out. The purpose of this study consists of 2 (two) things. First, outlining the urgency of preventing corruption in the use of village funds for direct cash assistance for handling Covid-19. Second, outlining alternative efforts that can be made to prevent corruption in the use of village funds for direct cash assistance for handling Covid-19. The results of this study indicate the urgency of preventing corruption in the use of village funds for direct cash assistance for handling Covid-19 for several reasons, including: the socio-economic conditions of rural communities who are vulnerable to Covid-19 transmission, data collection and distribution of direct cash assistance from village funds to vulnerable beneficiaries. there is corruption. Furthermore, alternative efforts that can be made to prevent corrupt practices in the use of village funds for direct cash assistance for village communities consist of 2 (two) things, namely: active involvement of village communities in special / incidental village deliberations, for validation / finalization of KPM data. Then optimize the supervisory role of the Village Consultative Body in the village / incidental deliberations.   Terganggunya kehidupan ekonomi masyarakat desa merupakan dampak Pandemi Covid-19 saat ini. Sehingga merugikan perolehan ekonomi masyarakat desa. Oleh karena itu, untuk meringankan dampak tersebut, maka Pemerintah mencanangkan program pemanfaatan dana desa untuk bantuan langsung tunai masyarakat desa. Akan tetapi, dalam pelaksanaan program tersebut memiliki celah terjadinya korupsi. Sehingga perlu dilakukan upaya untuk mencegah terjadinya korupsi tersebut, demi mengefektifkan pemberian bantuan langsung tunai kepada masyarakat. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pendekatan kasus, dan pendekatan undang-undang. Selanjutnya bahan hukum yang digunakan yakni bahan hukum primer dan sekunder. Kemudian dilakukan analisis secara kualitatif. Tujuan penelitian ini terdiri atas 2 (dua) hal. Pertama, menguraikan urgensi pencegahan korupsi dalam penggunaan dana desa untuk bantuan langsung tunai penanganan Covid-19. Kedua, menguraikan alternatif upaya yang dapat dilakukan dalam mencegah korupsi pengggunaan dana desa untuk bantuan langsung tunai penanganan Covid-19. Hasil penelitian ini menunjukan urgensi pencegahan korupsi dalam penggunaan dana desa untuk bantuan langsung tunai penanganan Covid-19 karena beberapa sebab, diantaranya: kondisi sosial ekonomi masyarakat desa yang rentan mengalami penularan Covid-19, pendataan dan penyaluran bantuan langsung tunai dana desa ke penerima manfaat rentan terjadi korupsi. Selanjutnya alternatif upaya yang dapat dilakukan untuk mencegah terjadinya praktik korupsi dalam penggunaan dana desa untuk bantuan langsung tunai masyarakat desa terdiri atas 2 (dua) hal, yakni: pelibatan aktif masyarakat desa dalam musyawarah desa khusus/insidentil, untuk validasi/finalisasi data KPM. Kemudian optimalkan peran pengawasan Badan Permusyawaratan Desa dalam musyawarah desa/insidentil tersebut.